E - COMMERCE CONVERSION MANAGEMENT AND OPTIMIZATION PRINCIPLES - Briška, Mareks; Ežmale, Sandra (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2021)
The conversion rate optimisation (CRO) essentially contains huge configuration capabilities, but it cannot be called a sophisticated marketing technique. Increased income, attracting new customers and reconnecting existing customers: these are just some of the benefits of an improved, efficient and constantly moving e-commerce site, so it is important to understand the conversion technique correctly before starting business on the Internet or performing optimization procedures. The objective of the research is to analyze the principles of e- commerce conversation management and optimisation. Two tasks have been set within the framework of the research: 1) to analyse the essence of e- commerce conversation optimisation; to describe conversion rate optimization steps.